2007
DOI: 10.1302/0301-620x.89b5.18183
|View full text |Cite
|
Sign up to set email alerts
|

The factors affecting outcome after non-vascular bone grafting and internal fixation for nonunion of the scaphoid

Abstract: This study identified variables which influence the outcome of surgical management on 126 ununited scaphoid fractures managed by internal fixation and non-vascular bone grafting. The site of fracture was defined by a new method: the ratio of the length of the proximal fragment to the sum of the lengths of both fragments, calculated using specific views in the plain radiographs. Bone healing occurred in 71% (89) of cases. Only the site of nonunion (p = 1 x 10(-6)) and the delay to surgery (p = 0.001) remained s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 30 publications
(43 reference statements)
0
56
0
1
Order By: Relevance
“…23) There were relatively large numbers of non-unions in these locations in our study. We found no significant difference in radiologic and functional outcomes between these two locations.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…23) There were relatively large numbers of non-unions in these locations in our study. We found no significant difference in radiologic and functional outcomes between these two locations.…”
Section: Discussionmentioning
confidence: 73%
“…22) Fracture location was assessed according to the fragment ratio method used by Ramamurthy et al on the postero-anterior radiograph. 23) Based on the fragment ratio, the location of the fracture was divided into the three thirds of the scaphoid. The middle third was further divided into proximal and distal halves.…”
Section: Methodsmentioning
confidence: 99%
“…The advantage of our material is in a relatively shortlasting nonunion (a mean of 10 months). It is suggested that if bone consolidation is not achieved within six months, operative treatment should be considered (3,4,31).…”
Section: Discussionmentioning
confidence: 99%
“…In Markowicz' study, in only 15 out of 48 patients (31%) was the fracture diagnosed, but in only in 2 (4%) was the diagnosis immediately after injury (1). Because of this, and because of the specific vascularity of scaphoid bone (the primary arterial supply enters the bone from distal pole), nonunion of the scaphoid is quite common, reaching a rate of up to 25-45% in proximal pole fracture (2,3). Operative treatment of scaphoid fracture decreases the rate of the late nonunion (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation